Hydrowl: A Hybrid Query Answering System for OWL 2 DL Ontologies - Stoilos, Giorgos (Web Reasoning and Rule Systems, 2014)
This system description paper introduces the OWL 2 query answering system Hydrowl. Hydrowl is based on novel hybrid techniques which in order to compute the query answers combine at run-time a reasoner ans1 supporting a (tractable) fragment of OWL 2 (e.g., OWL 2 QL and OWL 2 RL) with a fully-fledged OWL 2 DL reasoner ans2. The motivation is that if most of the (query answering) work is delegated to the (usually) very scalable system ans1 while the interaction with ans2 is kept to a bare minimum, then we can possibly provide with scalable query answering even over expressive fragments of OWL 2 DL. We discuss the system’s architecture and we present an overview of the techniques used. Finally, we present some first encouraging experimental results.